Human error in the engineering design process. - Busby, Jeremy S. (Professional Engineering Publishing, 2000)
A study was conducted of human error in the engineering process of 5 organisations that designed industrial equipment. Approximately 150 errors that had taken place were analysed individually and then coded according to the particular design activity that failed. Modes of error that were common to error in different activities were then identified. Among the primary modes of error were cases where designers failed to elicit the constraints and requirements presented by the outside world, but did so because they had fallacious beliefs that were nonetheless reasonable inferences from limited historical experience. Error was also associated 1) with the emergence of latent constraints when scaling up a design, 2) with refining designs that made them vulnerable to uncertainties in the external world, 3) with modifying existing designs whose rationale was obscure, and 4) with design tools which provided inadequate feedback for users learning by trial and error. The most promising way of reducing error may be to make designers more knowledgeable about the types of error accompanying different activities.